INFORMATION TECHNOLOGY SERVICES MANAGEMENT AUDIT USING THE COBIT AND ITIL FRAMEWORK - Risa Aulia Safitri; Nurul Mutiah; Ferdy Febriyanto (STMIK Royal, 2023)
Abstract: Utilization of IT can provide services to the community, encourage convenience in public services at a more affordable cost and performance efficiency. IT governance that includes leadership, organizational structure, and processes in its management ensures that IT is utilized as optimally as possible to meet current and future needs of the organization. The Population and Civil Registration Office of Kubu Raya Regency utilizes IT in carrying out public service activities using the SIPEMUDA Application. An information system audit is needed to improve system performance. In this study, using the Control Objective for Information and Related Technology (COBIT 2019) to determine whether the organization's needs have been supported by management and the Information Technology Infrastructure Library (ITIL 4) domain service management to determine suggestions for improvement. Capability level assessment in this study using COBIT Performance Management. The results of the capability assessment are that there are 6 processes reaching level 1, 33 processes reaching level 2, 28 processes reaching level 3, 18 processes reaching level 4, 7 processes reaching level 5 while the level that does not meet the capabilities is 19 processes. Furthermore, the results of process recommendations that do not meet the capabilities are prioritized using the Action Priority Matrix. Keywords: action priority matrix, cobit 2019, cobit performance management, itil 4, public service Abstrak: Pemanfaatan TI dapat memberikan pelayanan kepada masyarakat, mendorong kemudahan dalam pelayanan publik dengan biaya yang lebih terjangkau dan efisiensi kinerja. Tata kelola TI yang mencakup kepemimpinan, struktur organisasi, dan proses, dalam pengelolaannya untuk memastikan bahwa TI dimanfaatkan seoptimal mungkin memenuhi kebutuhan organisasi saat ini dan yang akan datang. Dinas Kependudukan dan Pencatatan Sipil Kabupaten Kubu Raya memanfaatkan TI dalam melaksanakan kegiatan pelayanan publik menggunakan Aplikasi SIPEMUDA. Audit sistem informasi diperlukan untuk meningkatkan kinerja sistem. Dalam penelitian ini, menggunakan Control Objective for Information and Related Technology (COBIT 2019) menentukan apakah kebutuhan organisasi sudah didukung oleh pengelolaan serta Information Technology Infrastructure Library (ITIL 4) domain service management untuk menentukan saran perbaikan. Penilaian level kapabilitas pada penelitian ini menggunakan COBIT Performance Management. Hasil penilaian kapabilitas yaitu terdapat 6 proses mencapai level 1, 33 proses mencapai level 2, 28 proses mencapai level 3, 18 proses mencapai level 4, 7 proses mencapai level 5 sedangkan level yang tidak memenuhi kapabilitas yaitu 19 proses untuk diberikan rekomendasi. Selanjutnya hasil rekomendasi proses tersebut diprioritaskan menggunakan Action Priority Matrix. Kata kunci: action priority matrix, cobit 2019, cobit performance management, itil 4, pelayanan publik.